Behavioral Repertoire of Basal Fungus-Growing Ant Sexuals (Hymenoptera: Formicidae) in the Parental Nest - Diniz, Eduardo A. [UNESP]; Bueno, Odair C.; Carlos, Amanda A. [UNESP] (California State University, 2010)
The present paper presents a range of observed behaviors with male and female alates of Attini ants in their parental nest. All described behaviors were observed in laboratory colonies of Apterostigma pilosum and Mycetarotes parallelus using micro video cameras. Each individual behavior was described and its frequency of occurrence was determined. Males of these species do not seem to rely upon workers as much as do males of Atta cephalotes. Moreover, female alates, unlike males, perform some of the same tasks as workers, such as caring for brood and preparing substrate for the symbiotic fungus. This set of behaviors, herein described for the first time with these species, were discussed in face of the actual role of alates inside parental colonies and at founding new ones.